2005
DOI: 10.1101/gr.3124505
|View full text |Cite
|
Sign up to set email alerts
|

Database of mRNA gene expression profiles of multiple human organs

Abstract: Genome-wide expression profiling of normal tissue may facilitate our understanding of the etiology of diseased organs and augment the development of new targeted therapeutics. Here, we have developed a high-density gene expression database of 18,927 unique genes for 158 normal human samples from 19 different organs of 30 different individuals using DNA microarrays. We report four main findings. First, despite very diverse sample parameters (e.g., age, ethnicity, sex, and postmortem interval), the expression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 26 publications
6
99
0
Order By: Relevance
“…The web interface offers a broad variety of options for data query, normalization, and visualization. It also offers an option to compare the expression profiles to our expression database of normal human tissues (25).…”
Section: Cancer Researchmentioning
confidence: 99%
“…The web interface offers a broad variety of options for data query, normalization, and visualization. It also offers an option to compare the expression profiles to our expression database of normal human tissues (25).…”
Section: Cancer Researchmentioning
confidence: 99%
“…4 A subset of these genes (n ϭ 34), which are specific to each diagnostic category, were selected for multiplex RT-PCR as seen in Table 2. In addition, several genes (n ϭ 5) differentially expressed in NB tumors and normal tissues from Son et al 7 and an unpublished result were also included in the assay (Table 2).…”
Section: Development Of Multiplex Rt-pcr Assay and Gene Selectionmentioning
confidence: 99%
“…It has been recently demonstrated that the expression profile of any randomly selected set of genes with a sufficient width (around 100) can correctly identify the kind of human tissue or organ from which the RNA was extracted. 14 Another unexpected conclusion is that these prognostic signatures very rarely include known progression-associated genes or clearly point to novel pathways or molecules associated with cancer progression. Therefore their exceptional prognostic and predictive value does not parallel an equal power to identify new potential targets for therapy and drug development.…”
mentioning
confidence: 99%